Perceived healthcare discrimination and well-being among older adults in the United States and Brazil - Angela R. Dixon; Leslie B. Adams; Tszshan Ma (Elsevier, 2022)
Despite well-documented evidence illustrating the relationship between discrimination and health, less is known about the influence of unfair treatment when receiving medical care. Moreover, our current knowledge of cross-national and racial variations in healthcare discrimination is limited in aging populations. This article addresses these gaps using two harmonized data sets of aging populations to clarify the relationship between healthcare discrimination and health in the United States and Brazil. We use nationally representative, harmonized data from the Health and Retirement Study in the United States and the Brazilian Longitudinal Study of Aging to examine and compare perceived discrimination in the healthcare setting and its relationship to self-rated health, depression diagnosis, and depressive symptoms across national contexts. Using Poisson regression models and population attributable risk percent estimates, we found that aging adults reporting healthcare discrimination were at higher risk of poor self-rated health, diagnosed depression, and depressive symptoms. Our results also suggest that reducing perceived healthcare discrimination may contribute to improved self-rated health and mental well-being in later life across racialized societies. In two comparative settings, we highlight the differential impact of healthcare discrimination on self-rated health and depression. We describe the implications of our study's findings for national public health strategies focused on eliminating discrimination in the healthcare setting, particularly among aging countries.